PROFIL LABORATORIUM IPA/BIOLOGI DAN KOMPETENSI GURU PENGELOLA LABORATORIUM SMA SWASTA DI KOTA PEKANBARU: Profile of Science / Biology Laboratory and Competency of Private High School Laboratory Management Teachers in the city of Pekanbaru - Laili Rahmi (UIR Press, 2018)
The study was conducted with the aim of wanting to find out the biology laboratory profiles in high schools, especially private. Research was carried out on private high schools in the city of Pekanbaru T.A 2016/2017, as the research sample was carried out in a random way. This research method was using surveys, documentation and observation. The research instrument used in this study was documentation guidelines for knowing the Biology Science lab in high school. The results of the data analyzed descriptively regarding the Profile of the Biological Science Laboratory of SMAS in Pekanbaru showed that the Biology Science laboratory conditions were undergraduate and S4 in 89.4% (Very good), and each indicator observed at the time of observation showed good laboratory conditions.